A rivalry‐based theory of gender diversity - Mawdsley, John Kenneth; Paolella, Lionel; Durand, Rodolphe (Strategic Management Journal, 2023)
Abstract Research Summary We offer a rivalry‐based perspective of gender diversity as a form of competitive action. We theorize that a firm adjusts its senior‐level female representation when they identify business opportunities that may be seized by demonstrating alignment to gender parity expectations. Examining U.S. corporate law firms and potential buyers of their services, we theorize and find that when the buyers of rivals of the focal firm increase their gender diversity, the focal firm responds by increasing its female partner representation. Reinforcing the strategic approach to managing gender diversity, we also show that a focal firm reduces its gender‐related response to rivals' buyers as the opportunity to attract those buyers decreases, and when the focal firm can use racial diversity as a credible substitute for gender diversity. Managerial Summary Do firms increase senior level gender diversity for normative or competitive reasons? We examine this question and test whether firms adjust their gender diversity to align with the gender diversity values of their competitors' clients. Our study shows that U.S. corporate law firms increase their level of female partners when the clients of their stronger competitors increase gender diversity in their executive rank. We also show that firms' gender diversity response weakens when there is a lower probability of luring those clients and when firms can offer racial diversity as a credible alternative signal of pro‐diversity values. Our competitive‐based view of gender diversity encourages managers to consider how and when proactive gender diversity improvement can be a mechanism for improving their firms' market position.